A case for Tartessian as a Celtic Language (Palaeohispanica. Revista sobre lenguas y culturas de la Hispania Antigua, 2019)
The paper discusses the south-western inscriptions and other linguistic evidence from the south-west of the Iberian Peninsula datable to the mid first millennium BC or specifically related to the kingdom of Tartessos. Some previously proposed Celtic explanations for Tartessian words are reconsidered and several new proposals are advanced. It is suggested that the density of probably Celtic forms is sufficient, particularly in the longer and better-preserved inscriptions, to support the hypothesis that the inscriptions are written in an Ancient Celtic language, rather than in some other language containing isolated Celtic names. This conclusion is consistent with recent proposals by archaeologists that the Atlantic Bronze Age had been Celtic speaking.